Methods Of Teaching English - D. Narmatov; Z. Abdullayeva (Euro Asian Journal Publishing, 2025)
In this article, the innovation of the English language teacher of general secondary schools information about ways to improve the quality of education is provided
Keywords: innovation; pedagogue-technologist; method